The Influence of Solar Control Films on Energy and Daylighting Performance by Means of Experimental Data and Preliminary Unsteady Simulations. (November 2015) - Moretti, Elisa; Belloni, Elisa; Lascaro, Elisa
Abstract: Solar control films were investigated as a strategy to improve thermal comfort, lighting conditions, and energy performance in non-residential buildings. The case study follows two adjacent similar offices with large window in the south-west façade of a building in Perugia, investigated by numerical and experimental approaches. The solar control films could strongly reduce the window heat gain (40-60%) and the indoor air temperature (1-1.5 °C), whereas the daily average illuminance level was lowered by about 50-60%. Finally the yearly cooling energy demand decreases of about 25% (only South- West façade) and 39% (all the façades), whereas the heating energy demand increases of about 10-15% thanks to solar control films.